Autosomal Dominant Epilepsy Syndrome Linked to 2p11 - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
A newly recognized autosomal dominant epilepsy syndrome with linkage to chromosome 2p11.1-q12.2 is described in an Italian pedigree of 8 patients reported from the Neurosciences Unit, Institute of Child Health and Great Ormond Street Hospital for Children, London, UK.